Voices outside law : Canada's justice system in the lives of survivors and victims of sexual violence - Roberts, Ramona, 1974- (2000)
Thesis (M.W.S.)--Memorial University of Newfoundland, 2000. Women's Studies Programme Bibliography: p. 232-245. This study examines the experiences of survivors and victims of sexual violence with the Canadian criminal justice system. The existing literature about the laws and the legal processing of sexual violence indicates that most cases of sexual violence are not reported, and that few of those reported end in conviction. The literature addressing the emotional impact of sexual violence on survivors, and the process of healing, indicates that legal proceedings are not seen by most survivors or therapists as a positive or even safe experience for survivors. -- Eight people who self-identified as survivors and/or victims of sexual violence participated in unstructured personal interviews. Grounded theory methodology was used to identify three main ways in which the criminal justice processing of sexual violence was felt to be hurtful to these survivors and victims: denial of victims' experiences of abuse, blaming of victims for having been abused, and violation of victims' privacy and autonomy. Participants' experiences and/ or fears of each of these injuries are described. The relationship between these experiences and the initial harms to respondents from sexual violence are also explored. Discussion focuses on the roles of abusers, societal responses to victims and Canada's laws on sexual violence in creating and aggravating the injuries common to survivors and victims. Some possible recommendations for improving victims' and survivors' perceptions and experiences of the criminal justice process are addressed. However, the most pressing need is for a widespread consultation of survivors and victims, to expand on the findings from this sample.